e-PADI: an iot-based paddy productivity monitoring and advisory system - M.A.F. Ismail; M. N. Md. Isa; S. N. Mohyar; M.I. Ahmad; M. N. M. Ismail; R. C. Ismail; A. Harun; S.A.Z. Murad (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Rice is source of food calories and protein.  This second most widely grown cereal crop is the staple food for more than half the world’s population especially in developing countries.  The ability of global rice production to meet population demands (now estimated at more than 5 billion and projected to rise to 8.9 billion by 2050) remains in uncertainty in the near future unless challenges in rice production are properly addressed [1-3]. This paper proposed an IoT (Internet of things)-based paddy productivity monitoring and advisory system Using Dash7 Wireless Network Protocol. All collected data will be stored in a database management system to enable users to retrieve data either from tablets, smartphones or computers. The heart of the system is the ATmega328p microcontroller that will control the payload of the wireless network of dash7 and read data from sensor nodes. Results show all data from sensor nodes in representation of graph for analysis purpose.